Psychometric Testing of the Czech Version of the Rapid Eating Assessment for Patients Questionnaire - Machálková, Lenka; Reiterová, Eva (Journal of nursing measurement, 2021)
BACKGROUND AND PURPOSE: The quantitative study focuses on the psychometric properties of the Rapid Eating Assessment for Patients (REAP) tool for assessing dietary habits. The aim of the study was to validate REAP and its factor structure, reliability, and validity. REAP was used for the first in patients with hypertension. METHODS: Language validation of REAP measurements into Czech language, test, retest, and pilot testing were performed. In addition, 420 patients were investigated, and exploratory confirmation factor analysis and Cronbach's alpha and Split-half coefficients were used. RESULTS: Five models with different number of items and identified factors were created. Reliability coefficients are satisfactory. The best results were achieved through the model created for a group of patients with hypertension. There were five factors extracted and described in words: Factor F1 was named "Meat consumption," factor F2 "Inappropriate food and activities for with hypertension (WH) patients," factor F3 "Consumption of dairy and fatty foods, "factor F4 "Consumption of sweet foods," and factor F5 "Appropriate food and activities for WH patients." CONCLUSION: The REAP questionnaire is a suitable tool for clinical practice use when assessing dietary habits in patients with hypertension.
Keywords: Hypertension; Česká republika; přijímání potravy; Eating; Aged; stravovací zvyklosti; Aged, 80 and over; lidé středního věku; senioři; dietary approaches to stop hypertension; lidé; Adult; Czech Republic; hypertenze; Middle Aged; dospělí; průzkumy a dotazníky; patient; Female; překlady; Factor Analysis, Statistical; senioři nad 80 let; reproducibility of results; Surveys and Questionnaires; Male; ženské pohlaví; Rapid Eating Assessment for Patients; Translations; Humans; mužské pohlaví; faktorová analýza statistická; psychometrie; Feeding Behavior; Psychometrics; feeding behavior